2019
DOI: 10.7554/elife.42697
|View full text |Cite
|
Sign up to set email alerts
|

A multiphase theory for spreading microbial swarms and films

Abstract: Bacterial swarming and biofilm formation are collective multicellular phenomena through which diverse microbial species colonize and spread over water-permeable tissue. During both modes of surface translocation, fluid uptake and transport play a key role in shaping the overall morphology and spreading dynamics. Here we develop a generalized two-phase thin-film model that couples bacterial growth, extracellular matrix swelling, fluid flow, and nutrient transport to describe the expansion of both highly motile … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 54 publications
3
67
0
Order By: Relevance
“…The copyright holder for this preprint this version posted October 26, 2020. ; https://doi.org/10.1101/2020.10.26.355560 doi: bioRxiv preprint RFP strain requires growth in a matrix-capable biofilm. A recent study showed that biofilm colony expansion in three dimensions depends heavily on extracellular matrix, while two-dimensional growth relies more on cell growth and division [43]. To test whether the mutualism between alrA and the matrix-deficient parent was dependent on three-dimensional growth, we grew co-cultures between an agar pad and a coverslip.…”
Section: Wild-type Cells Rescue Alra Knockdown In a Biofilm Colony Bymentioning
confidence: 99%
“…The copyright holder for this preprint this version posted October 26, 2020. ; https://doi.org/10.1101/2020.10.26.355560 doi: bioRxiv preprint RFP strain requires growth in a matrix-capable biofilm. A recent study showed that biofilm colony expansion in three dimensions depends heavily on extracellular matrix, while two-dimensional growth relies more on cell growth and division [43]. To test whether the mutualism between alrA and the matrix-deficient parent was dependent on three-dimensional growth, we grew co-cultures between an agar pad and a coverslip.…”
Section: Wild-type Cells Rescue Alra Knockdown In a Biofilm Colony Bymentioning
confidence: 99%
“…Paenibacillus dendritiformis [7] form dendritic protrusions, which can develop into highly branched structures. Bacillus subtilis [17,23] and pseudomonas [15,[24][25][26][27] have been shown to expand in either smooth fronts or dendritic patterns dependent on various chemical and physical factors. We and others have shown, for instance, that by simply varying the agar concentrations [15,26], adding external surfactants into the agar [15], or simply leaving the agar surface to dry for some time [15], the patterns of the colonies or swarms can vary from smooth to dendritic edges.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it may not be possible to predict from growing each species by itself what the joint reproductive output of a collective will be, or how robust such a collective will be to external biotic and abiotic perturbations. Microbial communities can also perform chemical transformations that would be impossible for one individual species to achieve [18], and some communities even display complex behaviours such as collective motion and electrochemical signalling, which have traditionally been associated with higher organisms [19,20].…”
mentioning
confidence: 99%